Detection and Co-occurrence of kdr (F1534C and S989P) Mutations in Multiple Insecticides Resistant Aedes aegypti (Diptera: Culicidae) in Nigeria. Issue 5 (12th August 2022) - Fagbohun, Ifeoluwa Kayode; Oyeniyi, Tolulope Amos; Idowu, Emmanuel Taiwo; Nwanya, Oge; Okonkwo, Felix; Adesalu, Kemi O; Jimoh, Romoke T; Oladosu, Yusuff; Otubanjo, Olubunmi Adetoro; Adeogun, Adedapo O
Abstract: The outbreak of yellow fever virus transmitted by Aedes aegypti has been of major concern in Nigeria, this mosquito also transmits several other arboviruses globally. The control of many vectors of mosquito-borne diseases relies heavily on the use of insecticides. Therefore, constant monitoring of insecticide resistance status and associated mechanisms is crucial within the local mosquito population. Here, we determined the resistance profile of adult Ae. aegypti from Majidun and Oke Ota communities, Ikorodu Local Government Area of Lagos State, Nigeria to different classes of insecticides using WHO procedures. The resistant phenotypes of Ae. aegypti were screened for the presence of kdr mutations F1534C, S989P, and V1016G, which have been implicated in insecticide resistance in yellow fever vectors. A high level of resistance to DDT and pyrethroids was recorded in Ae. aegypti in this study, although possible resistance to deltamethrin, one of the pyrethroids was reported in one of the locations. Resistance to bendiocarb was recorded in the Majidun community while Ae. aegypti in both locations were susceptible to malathion. The presence of F1534C mutation associated with DDT and deltamethrin resistance in Ae. aegypti population, and the presence of S989P mutation were detected singly and in co-occurrence with F1534C for the first time in Africa, while V1016G mutation was not detected in this study. The role of these mutations in resistance phenotype expressed in Ae. aegypti in larger populations needs to be established.